ASPECTOS BIOLÓGICOS Y ETOLÓGICOS DE CALLISPHYRIS MACROPUS NEWMAN (COLEOPTERA: CERAMBYCIDAE) EN ZARZAPARRILLA (RIBES NIGRUM Y RIBES RUBRUM) - Carrillo, R.; Neira, M.; Cifuentes, C.; Mundaca, N. (Acta Entomológica Chilena, 2022)
The seasonal cycle of Callisphyris macropus Newman (Coleóptera: Cerambyddae), under field conditions is described in this árdele. Samples were obtained from commercial plots of gooseberry, blaek currant and red currant in the IX and X Región, Chile. In currant, C macropus presents a biennial cycle. Ethological aspeets of oviposidon and larval behaviour in Ribes nigrum are indicated.